Tet2-mediated DNA demethylation regulates the proliferation and apoptosis of human leukemia K562 cells: DNA demethylation regulates K562 cells - Qiao, Yan; Zhou, Yanhua; Yang, Honglan; He, Zhixu; Fan, Anran (Cellular and Molecular Biology, 2023)
TET2 is a member of the TET protein family which is responsible for active DNA demethylation through catalyzing the successive oxidation of 5-methylcytosine (5mC) to 5-hydroxymethylcytosine (5hmC), 5-formylcytosine (5fC), and 5-carboxylcytosine (5caC), and mutations of Tet2 frequently lead to hematological malignancies. However, the relationship between Tet2-mediated demethylation and hematological malignancies is unclear. The human leukemia K562 cell line is an immortalized leukemia line that serves as an in vitro model of erythroleukemia. In this study, we investigated the effect of Tet2-mediated demethylation on the apoptosis and proliferation of human leukemia K562 cells and found that knockdown of Tet2 promoted and inhibited K562 cell proliferation and apoptosis, respectively, while upregulation of TET2 enzymatic activity via alpha-ketoglutaric acid (α-KG) had the opposite effects. Therefore, the Tet2 gene acts as a potential target for the treatment of leukemia, and small molecules that target the Tet2 gene may be used to screen antitumor drugs for hematological malignancies.